2003
DOI: 10.1097/00001813-200303000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol induces apoptosis in human leukemia cells via cytochrome c release and caspase activation

Abstract: Magnolol, isolated from the stem bark of Magnolia officnalis, was found to inhibit proliferation of human HL-60 cells and Jurkat T leukemia cells via inducing apoptosis in a dose- and time-dependent manner. By contrast, magnolol did not cause apoptosis in neutrophils and peripheral blood mononuclear cells of healthy donors. Apoptosis was determined by detection of DNA fragmentation in gel electrophoresis, morphological alternations by flow cytometry, quantification of phosphatidylserine externalization by Anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…18,19) Several reports have demonstrated that magnolol treatment does not affect the viability of normal cells such as human prostate epithelial cells and normal blood cells. 18,25) We also observed that magnolol showed no toxicity (<50 µM) in fibroblasts (NIH-3T3) (data not shown). Magnolol is probably a safe molecule for potential clinical use in cancer therapy.…”
Section: Discussionmentioning
confidence: 70%
“…18,19) Several reports have demonstrated that magnolol treatment does not affect the viability of normal cells such as human prostate epithelial cells and normal blood cells. 18,25) We also observed that magnolol showed no toxicity (<50 µM) in fibroblasts (NIH-3T3) (data not shown). Magnolol is probably a safe molecule for potential clinical use in cancer therapy.…”
Section: Discussionmentioning
confidence: 70%
“…Apoptosis may be partially attenuated by caspase-3 and -2 inhibitors. These results indicate that magnolol-induced apoptotic signaling was carried out through mitochondrial alterations to caspase-9 and that the downstream effector caspases were then activated sequentially (35).…”
Section: Targeting Cancer Cells By Caspase-mediated Apoptosismentioning
confidence: 81%
“…Magnolol induces the apoptosis of many human cancer cell lines, including lung squamous cancer CH-27 cells, HL-60 cells, colon cancer COLO 205 cells, and liver cancer HepG2 cells (34)(35)(36)(37)(38), but does not induce the apoptosis of bovine aorta endothelial BAE cells (38) or polymorphonuclear and mononuclear leukocytes (35). Honokiol induces the apoptosis of human lymphoid leukemia Molt 4B cells, CH27 cells, B-CLL cells, and RKO cells in a time-and dose-dependent manner (5,34,39,40).…”
Section: Targeting Apoptosis Pathways In Cancer With Magnolol and Honmentioning
confidence: 99%
“…Recently, attention has been paid to its anticancer action. Generally, lower concentrations of magnolol (3-40 mM) inhibit cell proliferation and high concentrations (80-100 mM) induce apoptosis of several cell lines derived from human cancers, including colon cancer, HepG2 hepatoma, leukemia cells, fibrosarcoma, melanoma, and squamous carcinoma [Lin et al, 2001[Lin et al, , 2002Ikeda and Nagase, 2002;Yang et al, 2003;Zhong et al, 2003]. In animals inoculated subcutaneously with B16-BL6 melanoma cells, magnolol effectively inhibits invasion and metastasis [Nagase et al, 2001;Ikeda and Nagase, 2002].…”
Section: Introductionmentioning
confidence: 99%